Induced spermiation of Pimelodus britskii (Teleostei: Pimelodidae) during the reproductive period - Damasceno, Danielle Zanerato [UNESP]; Krause, Ricardo Andrei; Adames, Mauricio Spagnolo; Neumann, Giovano; Gibathe, Anderson; Bombardelli, Robie Allan; Romagosa, Elizabeth (Wiley-Blackwell, 2017)
For the first time was characterized the semen of Pimelodus britskii, hormonally induced and non-induced induced, during the reproductive period. The experiment 1 was conducted with 12 fish per month, divided into: (i) induced with Carp Pituitary Extract (CPE), and (ii) without hormonal induction (testes macerated). The experiment 2 was conducted, with 30 fish, divided into groups for comparison of different doses of CPE and human Chorionic Gonadotrophin (hCG; T1: control; T2: 3.0mgkg(-1) CPE; T3: 0.5mgkg+3.0 mgkg(-1) CPE; T4: 0.5mgkg(-1)+7.0mgkg(-1) CPE; T5: 200UIkg(-1) hCG), the same fish were used every month, and the semen was collected by abdominal massage. In both, experiments were assessed the sperm motility and velocity by means of the CASA software. In experiment 1, the concentration of spermatozoids was significantly increase by application of CPE compared untreated males. The volume and motility decreased gradually until the end of the experiment, the highest values were recorded for treatment induced (0.49 +/- 0.25mL and 62.18, respectively). The same occurred to Gonadosomatic Index, showing the smallest value at the end of the reproductive period. The fish from experiment 2 released reduced volume of watery semen (0.1mL). The values of sperm concentration, motility velocity decreased gradually throughout the months. For P.britskii, the reproductive period influenced the production and sperm quality. Despite small seminal volume released the dose of 7.5mgkg(-1) of CPE proved effective.
Keywords: seminal characteristics; reproductive cycle; carp pituitary extract; human chorionic gonadotropin; semen production; semen quality